2021
DOI: 10.3233/ch-211164
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of intravascular perfusion based contrast-enhanced ultrasound LI-RADS in the evaluation of hepatocellular carcinoma

Abstract: BACKGROUND: The contrast-enhanced ultrasound (CEUS) liver imaging reporting and data system (LI-RADS) is a relative new algorithm for hepatocellular carcinoma (HCC) assessment. OBJECTIVE: To validate the diagnostic efficiency of the intravascular perfusion based CEUS LI-RADS for HCC. METHODS: Archives of 873 patients with focal liver lesions (FLLs) undergoing CEUS were reviewed, and target images were read by two sonologists independently according to the CEUS LI-RADS. The diagnostic performance was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…From another perspective, the specific physical, chemical, and biological features of contrast agents can result in potentially different patterns in imaging signs. The contrast agents used for CEUS manifest as intravascular microbubbles, which show clearer and more typical enhancement patterns of HCC and intrahepatic cholangiocarcinoma, and thus, may contribute to higher diagnostic accuracy and specificity ( 36 , 37 ). Moreover, since CEUS and CT/MRI rely on different diagnostic parameters due to distinct image acquisition techniques and the properties of contrast agents, a couple of studies have suggested that CEUS should be supplemented if results of more than 2 imaging techniques contradicted ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, the specific physical, chemical, and biological features of contrast agents can result in potentially different patterns in imaging signs. The contrast agents used for CEUS manifest as intravascular microbubbles, which show clearer and more typical enhancement patterns of HCC and intrahepatic cholangiocarcinoma, and thus, may contribute to higher diagnostic accuracy and specificity ( 36 , 37 ). Moreover, since CEUS and CT/MRI rely on different diagnostic parameters due to distinct image acquisition techniques and the properties of contrast agents, a couple of studies have suggested that CEUS should be supplemented if results of more than 2 imaging techniques contradicted ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were prospective ( 13 , 19 , 38 ) and 23 were retrospective ( 14 - 18 , 20 - 37 ). Of the studies, 10 used histopathology only as the reference standard ( 15 , 16 , 19 , 21 , 23 - 25 , 27 , 30 , 33 ) and 16 used both histopathology and imaging follow-up as the reference standard ( 13 , 14 , 17 , 18 , 20 , 22 , 26 , 28 , 29 , 31 , 32 , 34 - 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the index test and reference standard domain were satisfactory. In relation to the patient selection domain, two studies had a high risk of selection bias due to their case-control study designs ( 15 , 21 ), and seven studies had a unclear risk, as the inclusion criteria for the nodule size was not specified ( 13 , 22 , 25 , 27 , 32 , 33 , 39 ). In relation to the flow and timing domain, the quality of the included studies was relatively low, which might be due to the use of mixed reference standards (pathology and imaging diagnosis or pathology only) and unclear the time interval between the index test(s) and reference standards.…”
Section: Resultsmentioning
confidence: 99%
“…At least preliminary studies indicate an improved characterization of differently pronounced peri-tumoral microvascularization with high-resolution contrast imaging in CEUS supplemented by parametric false-color imaging [ 2 ]. According to the Liver Imaging Reporting and Data System (LI-RADS) classification, the detection of small tumor foci in only arterial hypercontrast up to 10 mm, a reliable differentiation of adenomas or regressively altered tumors, and the detection of all tumor foci in poor acoustic conditions may require complementary imaging with CT and or MERT with liver-specific contrast agent as an alternative to histologic confirmation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%